Assessment of Primary School Science Teachers’ Knowledge towards Health Promotion in Baghdad City - Faraj, raad; Khalifa, mohammed (Iraqi National Journal of Nursing Specialties, 2010)
Objective: Assessment of primary schools science teachers’ knowledge towards health promotion in Baghdad City. Methodology: A descriptive study was conducted at (100) primary school at Al-Rasafa, and Al-Karkh sectors in Baghdad City, from November 29th 2007 to January 20th 2009. A probability stratified random sample of (100) teachers who teach science subject was selected, and had at least one year of employment in the teaching field. A questionnaire format was used which was consisted of (2) parts. The overall number of the items included in the questionnaire were (205) items. The first part was related to the demographic data of the teachers, the second part (six sections) was concerned with teachers’ knowledge about health promotion. Reliability and validity of questionnaire was estimated through a pilot study. Data were analyzed through the application of descriptive statistical analysis which included; frequency and percentage, and the application of inferential statistical analysis which included; mean of score, Pearson correlation coefficient and Chi-square test. Results. The study revealed that teachers have acquired moderate level of knowledge about nutrition, communicable diseases, immunization and vaccination, injuries and accidents, obesity, acute illness problems, dental problems, social and psychological development, water and lead pollution, radiation, noise problems, waste disposal and plants problems. Concerning the relationship between teachers’ knowledge and their demographic characteristics, data analysis has showed that there is no association between teachers’ knowledge and their ages, gender, and sectors. While, there is a significant associations between teachers’ knowledge and their educational level, years of employment and training sessions. Recommendations: The study recommends that there is a need for health promotion-oriented education program which can be designed, constructed and presented to primary school teachers with great emphasis on all aspects of health promotion. Furthermore, teacher can be nominated and encouraged to actively participate in health promotion training sessions. Also, the importance of a collaborative work which can be initiated between the Ministry of Education and the Ministry of Health to create facilities for the implementation of health promotion oriented education program.